2020
DOI: 10.1002/cmdc.202000128
|View full text |Cite|
|
Sign up to set email alerts
|

Design and Synthesis of Fluorescent Methylphenidate Analogues for a FRET‐Based Assay of Synapsin III Binding

Abstract: We previously described synapsin III (Syn III) as a synaptic phosphoprotein that controls dopamine release in cooperation with α‐synuclein (aSyn). Moreover, we found that in Parkinson's disease (PD), Syn III also participates in aSyn aggregation and toxicity. Our recent observations point to threo‐methylphenidate (MPH), a monoamine re‐uptake inhibitor that efficiently counteracts the freezing‐gait characteristic of advanced PD, as a ligand for Syn III. We have designed and synthesised two different fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Interestingly, we previously demonstrated that Syn III ko mice do not present motility improvement following acute i.p. administration of MPH [ 11 , 12 ], in agreement with our findings supporting that MPH can bind Syn III and with evidence showing that the efficacy of MPH is perturbed in ADHD patients with Syn III polymorphisms [ 10 , 12 ]. Still, consistently with the reduction of cocaine-induced facilitation of DA release in SN pr brain slices from Syn III-deficient mice [ 1 ], we also found that these animals do not even present a locomotor response following acute cocaine administration [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, we previously demonstrated that Syn III ko mice do not present motility improvement following acute i.p. administration of MPH [ 11 , 12 ], in agreement with our findings supporting that MPH can bind Syn III and with evidence showing that the efficacy of MPH is perturbed in ADHD patients with Syn III polymorphisms [ 10 , 12 ]. Still, consistently with the reduction of cocaine-induced facilitation of DA release in SN pr brain slices from Syn III-deficient mice [ 1 ], we also found that these animals do not even present a locomotor response following acute cocaine administration [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, certain human Syn III gene (SYN3) polymorphisms associate with ADHD onset and influence the response to the most effective ADHD treatment, methylphenidate (MPH), a monoamine reuptake inhibitor which binds Syn III [ 4 , 10 , 11 , 12 ]. This hints that Syn III may control the development of mDN.…”
Section: Introductionmentioning
confidence: 99%
“…administration of MPH, consistently with ndings showing that the action of this drug can be mediated by Syn III [12,13].…”
Section: Discussionsupporting
confidence: 83%
“…Certain human Syn III gene polymorphisms associate with ADHD onset and can even in uence the response to the most effective ADHD treatment, methylphenidate (MPH), a key modulator of dopaminergic neurotransmission that, as we recently showed, can bind Syn III [9,[11][12][13]. ADHD is characterized by an impaired development of dopaminergic neurons, re ected by a marked alteration in brain dopamine (DA) synthesis and dopaminergic dysregulations [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…10 Consistently, by generating a fluorescent cell permeable MPH derivative, we were able to detect a direct interaction between MPH and Syn III in cells in culture by fluorescence resonance energy transfer (FRET). 14 In addition, we observed that MPH promotes the interaction between Syn III and a specific a-helical conformation of a-syn owning low aggregation propensity. 10 This effect is contrary to that of Syn III, which instead appears to promote a-syn aggregation.…”
Section: Introductionmentioning
confidence: 72%